Problem In Defining Quantum Leadership – A Systematic Literature Review (Journal of Namibian Studies : History Politics Culture, 2023)
Objective: The paper offers an analysis and definition of the concept of Quantum leadership in the light of current socio-economic trends. The following research questions were posed: “How is quantum leadership understood?” and “What elements comprise its definition?”. The definitions of quantum leadership place the term in a range of categories: as a characteristic, a behaviour, a process, a role relationship, or a position in an organisational structure. It has been analysed through multiple paradigms, including classical, transactional, transformational, situational, and service leadership. It is not clear at present which definition is dominant, nor which   research methods have been used to determine its constituent elements.Research Design & Methods: A critical and systematic literature review covering publications that appeared in the years 2010–2020; 55 full-text indexed publications were analysed from the Scopus database.Findings: The research draws together and organises definitions of leadership that have appeared in the last 10 years in the publications indexed from the Scopus database. The  authors also put100 Justyna Bugaj, Alla Sulymaforward their own definition of quantum leadership from the perspective of management and quality sciences.Implications / Recommendations: Organising the definition of quantum leadership allows the authors to understand the diversity and complexity  which have a positive impact on building, strengthening and developing leadership. The study also brings to light areas and directions for further research. in the gender of managers or discrepancies in the perception of leadership resulting from publications from various geographic and cultural regions.Contribution: Arranging the existing definitions of quantum leadership and its components from the perspective of management and quality sciences; demonstrating that a qualitative approach is increasingly  used in leadership research.